Restructuration Fatty Acid Oil Castor Being Cocoa Butter Substitute Through Dehydration Reaction Castor Oil And This Interesterification With Coconut Oil - Ribka J Sirait; Marham Sitorus (Universitas Negeri Medan, 2021)
The purpose of this research to restructuring its acid fatty oils castor result of dehydration with coconut oil through the process interesterification to produce cocoa butter substitute (CBS). Coconut oil is obtained from coconut milk by heating it slowly over low heat. The resulting coconut oil has a FFA is 1.667%, a peroxide is 10.229 MekO2 / Kg and an iodine is 7,7080 gI2/100g, which meets the second quality standard according to SNI 01-3741-2002. The restructuring was carried out by interesterification of dehydrated castor oil with coconut oil with a ratio (50:50); (60:40); (70:30); (80:20) dan(90:10)with a NaOCH3 catalyst. The results showed that the interesterification of dehydrated castor oil with coconut oil with a ratio (50:50) was the most optimal ratio with a melting point of 33 oC which corresponds to cocoa oil (32 oC-35 oC) and contain omega-6 fats (linoleic acid).